Estimation error in sound velocity depending on size of target scatterer. (28th April 2021) - Nakayama, Aoi; Mori, Shohei; Arakawa, Mototaka; Kanai, Hiroshi
Abstract: The quality of ultrasonic images can be improved by estimating the sound velocity accurately. Our previous study proposed a method to estimate the sound velocity based on the difference between the reception times of radiofrequency signals received by elements in an ultrasonic probe. Because the method assumed an ideal point scatterer as the target, the estimation error in the sound velocity increased with an increase in the target scatterer size. In the present study, the effect of the target scatterer size on the estimation method was examined, and the relationship between the size of the target scatterer and the estimation error in the sound velocity was quantified. Through simulations and basic experiments, it was confirmed that the estimation error was caused by the change in the reception time from the target surface and that the estimation error depended on the depth and size of the target scatterer.